C-Reactive Protein: Clinical Relevance and Interpretation From Medical Laboratory and Health Informatics Perspectives - Alanazi, Salman Saad Thamer; Sultan Hadi Alanazi; Tariq Mukhaymir Hamdan Alharbi; Alawyah Abker Ahmed Ageel; Mariam swilam daghash alqahtani (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> C-reactive protein (CRP) is a highly conserved acute-phase biomarker synthesized by hepatocytes in response to inflammatory stimuli, primarily mediated by IL-6. It exists in pentameric (pCRP) and monomeric (mCRP) isoforms, each with distinct immunological functions. CRP plays an essential role in innate immunity through ligand binding, complement activation, and phagocytic enhancement. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To provide a comprehensive review of the clinical relevance, diagnostic applications, and factors affecting CRP measurement from medical laboratory and health informatics perspectives. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes experimental, clinical, and epidemiological findings regarding CRP structure, regulation, clinical utility, diagnostic techniques, and interfering variables. It also incorporates FDA-cleared assay technologies and point-of-care innovations. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CRP demonstrates rapid kinetic response, rising within hours of inflammation and declining promptly upon resolution. Its elevations correlate with infectious, autoimmune, traumatic, and neoplastic conditions. High-sensitivity CRP (hsCRP) enables cardiovascular risk stratification by detecting low-grade inflammation. Elevated CRP levels also predict venous thromboembolism risk, cancer propensity, heart failure progression, and frailty in aging populations. Numerous factors—including medications, lifestyle, genetics, and comorbidities—modulate CRP concentrations and complicate interpretation. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> CRP remains a vital biomarker for diagnosing and monitoring inflammation across diverse clinical scenarios. Its usefulness depends on proper contextual interpretation, integration with clinical findings, and awareness of interfering variables. Advances in diagnostic technology have improved CRP measurement accuracy, accessibility, and clinical value.